A cucurbit[5]uril analogue from dimethylpropanediurea–formaldehyde condensation. Issue 14 (13th January 2015) - Jiang, Xiaoqing; Yao, Xuyang; Huang, Xinghua; Wang, Qiaochun; Tian, He
Abstract : A new cucurbit[5]uril-like macrocycle has been synthesized and shows good solubility in water and organic solvents. Abstract : A new host Me10 TD[5] was prepared for the first time from propanediurea–formaldehyde condensation. Me10 TD[5] is soluble in both water and common organic solvents, and binds protonated amines in a 1 : 2 stoichiometry in H2 O with the K 1 and K 2 values on the order of 10 3 M −1 . The self-assembly of Me10 TD[5] with 1, 4-xylylene diamine dihydrochloride results in the formation of a linear supramolecular polymer.